Out‐of‐pocket medical costs and third‐party healthcare costs for children with Down syndrome. Issue 3 (14th December 2016) - Kageleiry, Andrew; Samuelson, David; Duh, Mei Sheng; Lefebvre, Patrick; Campbell, John; Skotko, Brian G.
Abstract : Prior analyses have estimated the lifetime total societal costs of a person with Down syndrome (DS); however, no studies capture the expected medical costs that patients with DS can expect to incur during childhood. The study utilized the OptumHealth Reporting and Insights administrative claims database from 1999 to 2013. Children with a diagnosis of DS were identified, and their time was divided into clinically relevant age categories. Patients with DS in each age category were matched to controls without chromosomal conditions. Out‐of‐pocket medical costs and third‐party expenditures were compared between the patient‐age cohorts with DS and matched controls. Patients with DS had significantly higher mean annual out‐of‐pocket costs than their matched controls within each age and cost category. Total annual incremental out‐of‐pocket costs associated with DS were highest among individuals from birth to age 1 ($1, 907, P  < 0.001). The main drivers of the incremental out‐of‐pocket costs associated with DS were inpatient costs in the 1st year of life ($925, P  <  0.001) and outpatient costs in later years (ranging $183–$623, all P  < 0.001). Overall, patients with DS incurred incremental out‐of‐pocket medical costs of $18, 248 between birth and age 18 years; third‐party payers incurred incremental costs of $230, 043 during the same period. Across all age categories, mean total out‐of‐pocket annual costs were greater for individuals with DS than those of matched controls. On average, parents of children with DS pay an additional $84 per month for out‐of‐pocket medical expenses when costs are amortized over 18 years. © 2016 Wiley Periodicals, Inc.